A change in supply chain information for Swedish process industries and its consequence on a changed development focus. (6th December 2005) - Chroneer, Diana
How can process industries cope when there is a need for information change in product development? This paper focuses on examining if a changed development focus in process industry can be supported by an integration of supply chain information in product development. This is achieved by focusing on two theoretical perspectives, namely, technology management and supply chain management. The research is based on case studies and a survey addressing companies in various process industries. The paper reveals that an analysis of the information that flows in the entire supply chain can help managers obtain a better understanding of what new competences and knowledge are required in product development. The need for this new type of information can be further formalised by building networks that act like a support to product development. This can be one integration sector between the two theoretical perspectives: technology management and supply chain management.